THE URGENCY OF LEARNING CITIZENSHIP EDUCATION IN HIGHER COLLEGE IN FORMING DEMOCRATIC ATTITUDES IN STUDENTS - Andrian, Andrian (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aims to describe the urgency of learning civics education in tertiary institutions in forming democratic attitudes in students. This research uses a qualitative approach with a literature study method. Data sources are taken from credible pages, including Sinta and Google Scholar. The results of this study indicate that civic education helps shape the morality of university-level students by covering three aspects. Namely, the first is the moral concept, which includes awareness of democratic life, understanding of democratic material, appreciation of the benefits of democracy, happy reasons and democratic practices, and self-introspection in democracy. Second, moral attitudes include a sense of freedom of life, freedom of opinion, empathy for others, pleasure in deliberations, self-control of freedom, and upholding and respecting the views of others. Third, moral behavior includes respecting democratic life, the will to live in a democracy, and the habit of being democratic with others.